Authigenic carbonate burial in the Late Devonian–Early Mississippian Bakken Formation (Williston Basin, USA). Issue 4 (29th January 2020) - Davis Barnes, Ben; Husson, Jon M.; Peters, Shanan E.
Abstract: Late Devonian (Famennian) marine successions globally are typified by organic‐rich black shales deposited in anoxic and euxinic waters and the cessation of shelf carbonate sedimentation. This global 'carbonate crisis', known as the Hangenberg Event, coincides with a major extinction of reef‐building metazoans and perturbations to the global carbon cycle, evidenced by positive carbon‐isotope excursions of up to 4‰. It has been suggested that authigenic carbonate, formed as cements in sedimentary pore spaces during early burial diagenesis, is a significant mass fraction of the total global carbon burial flux, particularly during periods of low oxygen concentration. Because some authigenic carbonate could have originated from remineralization of organic carbon in sediments, it is possible for this reservoir to be isotopically depleted and thereby drive changes in the carbon isotopic composition of seawater. This study presents bulk isotopic and elemental analyses from fine‐grained siliciclastics of the Late Devonian–Early Mississippian Bakken Formation (Williston Basin, USA) to assess the volume and isotopic composition of carbonates in these sediments. Carbonate in the Bakken black shales occurs primarily as microscopic disseminated dolomite rhombs and calcite cements that, together, comprise a significant mass‐fraction ( ca 9%). The elemental composition of the shales is indicative of a dynamic anoxic to sulphidic palaeoenvironment, likely supported by a fluctuating chemocline. Despite forming in an environment favourable to remineralization of organic matter and the precipitation of isotopically depleted authigenic carbonates, the majority of carbon isotope measurements of disseminated carbonate fall between −3‰ and +3‰, with systematically more depleted carbonates in the deeper‐water portions of the basin. Thus, although there is evidence for a significant total mass‐fraction of carbonate with contribution from remineralized organic matter, Bakken authigenic carbonates suggest that Famennian black shales are unlikely to be sufficiently 13 C‐depleted relative to water column dissolved inorganic carbon to serve as a major lever on seawater isotopic composition.